Improving species status assessments under the U.S. Endangered Species Act and implications for multispecies conservation challenges worldwide. Issue 6 (28th June 2021) - Noss, Reed F.; Cartwright, Jennifer M.; Estes, Dwayne; Witsell, Theo; Elliott, Gregg; Adams, Daniel; Albrecht, Matthew; Boyles, Ryan; Comer, Patrick; Doffitt, Chris; Faber‐Langendoen, Don; Hill, JoVonn; et al.
Abstract: Despite its successes, the U.S. Endangered Species Act (ESA) has proven challenging to implement due to funding limitations, workload backlog, and other problems. As threats to species survival intensify and as more species come under threat, the need for the ESA and similar conservation laws and policies in other countries to function efficiently has grown. Attempts by the U.S. Fish and Wildlife Service (USFWS) to streamline ESA decisions include multispecies recovery plans and habitat conservation plans. We address species status assessment (SSA), a USFWS process to inform ESA decisions from listing to recovery, within the context of multispecies and ecosystem planning. Although existing SSAs have a single‐species focus, ecosystem‐based research can efficiently inform multiple SSAs within a region and provide a foundation for transition to multispecies SSAs in the future. We considered at‐risk grassland species and ecosystems within the southeastern United States, where a disproportionate number of rare and endemic species are associated with grasslands. To initiate our ecosystem‐based approach, we used a combined literature‐based and structured World Café workshop format to identify science needs for SSAs. Discussions concentrated on 5 categories of threats to grassland species and ecosystems, consistent with recommendations to make shared threats a focus of planning under the ESA: (1) habitat loss, fragmentation, and disruption of functional connectivity; (2) climate change; (3) altered disturbance regimes; (4) invasive species; and (5) localized impacts. For each threat, workshop participants identified science and information needs, including database availability, research priorities, and modeling and mapping needs. Grouping species by habitat and shared threats can make the SSA process and other planning processes for conservation of at‐risk species worldwide more efficient and useful. We found a combination of literature review and structured discussion effective for identifying the scientific information and analysis needed to support the development of multiple SSAs. Article impact statement : Species status assessments can be improved by an ecosystem‐based approach that groups imperiled species by shared habitats and threats. Abstract : Mejoramiento de la Evaluación del Estado de una Especie bajo el Acta de Especies en Peligro de los Estados Unidos y Sus Consecuencias para los Retos de la Conservación Multiespecie a Nivel Mundial Resumen: A pesar de su éxito, el Acta de Especies en Peligro de los E.U.A. (AEP) ha sido un reto de implementación por las limitaciones en su financiamiento, el retraso en la carga de trabajo y otros problemas. Conforme se intensifican las amenazas a la supervivencia de las especies y más especies resultan amenazadas, aumenta la necesidad de que la AEP y las políticas similares de otros países funcionen efectivamente. Los intentos por parte del Servicio Estadounidense de Pesca y Fauna (SEPF) para optimizar las decisiones de la AEP incluyen planes multiespecie de recuperación y planes de conservación de hábitat (PRH). Abordamos la evaluación del estado de las especies (EEE), un proceso del SEPF para orientar las decisiones del AEP desde el listado hasta la recuperación, dentro del contexto de la planeación multiespecie y de ecosistemas. Aunque las EEE existentes tienen un enfoque sobre una única especie, la investigación basada en el ecosistema puede orientar eficientemente a múltiples EEE dentro de una región y proporcionar una base para la transición a las EEE multiespecie en el futuro. Consideramos a las especies y los ecosistemas en riesgo de los pastizales del sureste de los Estados Unidos, en donde un número desproporcionado de especies raras y endémicas está asociado con los pastizales. Para iniciar nuestra estrategia basada en el ecosistema, usamos un formato de taller de World Café estructurado y basado en la literatura para identificar la necesidad de tener EEE. Las discusiones se centraron en cinco categorías de amenazas para las especies y ecosistemas de los pastizales, consistentes con las recomendaciones para volver a las amenazas compartidas un foco de la planeación bajo la AEP: (1) pérdida del hábitat, fragmentación y disrupción de la conectividad funcional; (2) cambio climático; (3) regímenes alterados de perturbación; (4) especies invasoras; y (5) impactos localizados. Para cada amenaza, los participantes del taller identificaron las necesidades científicas y de información, incluyendo la disponibilidad de bases de datos, prioridades de la investigación y necesidades de modelado y mapeado. La agrupación de las especies por hábitat y amenaza compartida puede hacer más eficientes y útiles el proceso de EEE y otros procesos de planeación de la conservación de especies en riesgo a nivel mundial. Encontramos una combinación de revisiones bibliográficas y discusiones estructuradas para identificar la información y el análisis necesarios para respaldar el desarrollo de múltiples EEE. 【摘要】: 尽管《美国濒危物种法案》 (U.S. Endangered Species Act, ESA) 已取得一定成功, 但由于资金限制、工作量积压及其它问题, 该法案的实施仍面临挑战。随着威胁的加剧和受到威胁的物种增加, 人们对于 ESA 及其它国家类似的保护法律和政策发挥有效作用的需求也越来越强烈。同时, 美国鱼类及野生动物管理局也在努力简化包括多物种恢复计划和栖息地保护计划在内的ESA决策过程。本研究以多物种和生态系统规划为背景, 进行了物种状态评估, 这是美国鱼类及野生动物管理局为物种从列入名录到恢复的一系列ESA决策提供信息的过程。现有的物种状态评估侧重于单一物种, 而基于生态系统的研究则可以有效地指导一个区域内多个物种状态评估过程, 并为未来向多物种状态评估过渡提供基础。本研究关注美国东南部濒危的草地物种和生态系统, 该地区草地稀有种和特有种的数量不成比例得高。为了实施基于生态系统的方法, 我们将基于文献和结构化世界咖啡馆研讨会的形式相结合, 以确定物种状态估计的科学需求。我们集中讨论了草地物种和生态系统面临的5类威胁, 并建议将共同存在的威胁作为ESA的规划重点, 这些威胁包括 (1) 栖息地丧失、破碎化和功能连接度中断; (2) 气候变化; (3) 干扰情况变化; (4) 入侵物种; (5) 局部地区的影响。研讨会参与者确定了每种威胁的科学需求和信息需求, 包括数据库可用性、优先研究内容以及建模和测绘需求。根据栖息地和共同威胁对物种进行分组, 可以使物种状态评估过程和全球其它濒危物种保护的规划过程更加有用和高效。我们发现, 将文献综述与结构化讨论相结合, 可以有效地确定支持多个物种状态评估发展所需的科学信息和分析。【翻译: 胡怡思; 审校: 聂永刚】